2020
DOI: 10.3389/fneur.2020.00990
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Deficits in Animal Models of Blast Traumatic Brain Injury

Abstract: Blast exposure has been identified to be the most common cause for traumatic brain injury (TBI) in soldiers. Over the years, rodent models to mimic blast exposures and the behavioral outcomes observed in veterans have been developed extensively. However, blast tube design and varying experimental parameters lead to inconsistencies in the behavioral outcomes reported across research laboratories. This review aims to curate the behavioral outcomes reported in rodent models of blast TBI using shockwave tubes or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 134 publications
(183 reference statements)
2
23
0
Order By: Relevance
“…The early recovery in foot-faults (3 dpi) is potentially due to abatement of the initial insult of tissue edema, which follows a similar time course [ 45 ]. Many studies of cortical brain injury, such as stroke and TBI, have reported early recovery of deficits and been extensively reviewed [ 46 , 47 ]. In a model of stroke, behavioral recovery corresponded strongly with blood flow adjacent to the injury site and related to vessel density [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The early recovery in foot-faults (3 dpi) is potentially due to abatement of the initial insult of tissue edema, which follows a similar time course [ 45 ]. Many studies of cortical brain injury, such as stroke and TBI, have reported early recovery of deficits and been extensively reviewed [ 46 , 47 ]. In a model of stroke, behavioral recovery corresponded strongly with blood flow adjacent to the injury site and related to vessel density [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“… 28 In a clinical study, 50% of veterans exposed to bTBI experienced anxiety disorders. 29 , 30 Anxiety disorders in animal models were characterized by increased arousal, expectancy, autonomic and neuroendocrine activation, as well as a transition from ongoing behaviors to an escape or other defensive behaviors. 31 Anxiety-like behaviors have been reported 3 months after repetitive, but not single, impact acceleration-induced mTBI in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental models of TBI have been developed with the goal of investigating the mechanisms of primary and secondary injury sequelae (Tables 1 and 2 and refs. [22][23][24][25][26][27].…”
Section: Tbi Pathophysiology and Long-term Consequencesmentioning
confidence: 99%